QTc Prolongation in Veterans With Heroin Dependence on Methadone Maintenance Treatment - Hassamal, Sameer (Int J High Risk Behav Addict, 2015)
BACKGROUND: QTc prolongation and Torsade de Ppointes have been reported in patients on methadone maintenance. OBJECTIVES: In this study, QTc was compared before and after the veteran (n = 49) was on a stable dosage of methadone for 8.72 ± 4.50 years to treat heroin dependence. Risk factors were correlated with the QTc once the veteran was on a stable dose of methadone. Differences in the clinical risk factors in subgroups of veterans with below and above mean QTc change was compared. PATIENTS AND METHODS: ECG data was obtained from a 12-lead electrocardiogram (pre-methadone and on methadone) on 49 veterans. Data and risk factors were retrospectively collected from the medical records. RESULTS: The mean QTc at baseline (pre-methadone) was 426 ± 34 msec and after being on methadone for an average of 8.72 ± 4.50 years was significantly higher at 450 ± 35 msec. No significant relationships were found between QTc prolongation and risk factors except for calcium. The methadone dosage was significantly higher in veterans with a QTc change above the mean change of ≥ 24 msec (88.48 ± 27.20 mg v.s 68.96 ± 19.84 mg). None of the veterans experienced cardiac arrhythmias. CONCLUSIONS: The low complexity of medical co-morbidities may explain the lack of a significant correlation between any risk factor with the QTc except calcium and methadone dosage. The absence of TdP may be explained by the low prevalence of QTc values > 500 msec as well as the retrospective design of the study. During long-term methadone treatment, there was a slight increase in the QTc interval but we did not find evidence of increased cardiac toxicity as a reason for treatment termination.